2021
DOI: 10.1186/s12913-021-06962-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an influenza vaccination campaign targeting pregnant women in 27 clinics in two provinces of South Africa, 2015 – 2018

Abstract: Introduction Despite prioritization, routine antenatal influenza vaccine coverage is < 16% in South Africa. We aimed to describe maternal influenza vaccine coverage in 27 antenatal clinics (ANCs) in Gauteng and Western Cape (WC) Provinces, where in collaboration with the Department of Health (DoH), we augmented the annual influenza vaccination programme among pregnant women. Methods From 2015 through 2018, 40,230 additional doses of influenza va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…[2] South Africa's influenza season typically occurs during the winter months (~May September). [3] The 2021 influenza season coincided with the country's third COVID 19 epidemic wave, raising the possibility of intersecting incidences of COVID19 and influenza. Influenza and COVID19 infections cause similar symptoms, yet have vastly different treatment and management approaches.…”
Section: Sharp Increase In Influenza a Infections In Limpopo: A Call ...mentioning
confidence: 99%
“…[2] South Africa's influenza season typically occurs during the winter months (~May September). [3] The 2021 influenza season coincided with the country's third COVID 19 epidemic wave, raising the possibility of intersecting incidences of COVID19 and influenza. Influenza and COVID19 infections cause similar symptoms, yet have vastly different treatment and management approaches.…”
Section: Sharp Increase In Influenza a Infections In Limpopo: A Call ...mentioning
confidence: 99%
“…5,7,26 Pregnant women are at an increased risk for severe illness from COVID-19 compared to age-matched women who are not pregnant. 5,19,26 Severe illness includes an increased risk of respiratory failure, requiring hospitalisation, intensive care unit admissions and mechanical ventilation, or illness that results in death. 5,19,26 Pregnant women are also at increased risk for stillbirths and preterm labour and in some cases, thrombotic events and pre-eclampsia.…”
Section: Covid-19 Vaccinationmentioning
confidence: 99%
“…However, recent studies have shown that dedicated antenatal influenza vaccination campaigns in selected sites in SA can reduce the severity of influenza while remaining cost-effective. 19 , 20 …”
Section: Routinely Recommended Vaccines In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations